2021
DOI: 10.1186/s12875-021-01445-5
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary treatment of anxiety in primary care: a systematic review and meta-analysis of outcomes in countries with universal healthcare

Abstract: Background Anxiety disorders are highly prevalent mental health conditions and are managed predominantly in primary care. We conducted a systematic review and meta-analysis of psychological and pharmacological treatments in countries with universal healthcare, and investigated the influence of treatment provider on the efficacy of psychological treatment. Method PubMed, Cochrane, PsycINFO, CINAHL, and Scopus were searched in April 2017 for controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Thus, the findings of this study using real-world data have significant implications for the dissemination of MHN-led CBT in routine practice. Furthermore, a previous study indicated that CBT for anxiety disorders is more effective when provided by psychiatrists or clinical psychologists than when provided by MHNs (Parker et al, 2021). Despite this, in terms of within-group effect size, our results were comparable to those of other studies in which mental health professionals other than MHNs delivered psychological interventions (including CBT) in a routine care setting.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Thus, the findings of this study using real-world data have significant implications for the dissemination of MHN-led CBT in routine practice. Furthermore, a previous study indicated that CBT for anxiety disorders is more effective when provided by psychiatrists or clinical psychologists than when provided by MHNs (Parker et al, 2021). Despite this, in terms of within-group effect size, our results were comparable to those of other studies in which mental health professionals other than MHNs delivered psychological interventions (including CBT) in a routine care setting.…”
Section: Discussionsupporting
confidence: 73%
“…However, service users' access to CBT in Japan is generally suboptimal owing to the scarcity of CBT providers under the health insurance scheme, which requires CBT to be only provided by skilled and experienced psychiatrists (Ono, 2011). Research has shown that psychological treatments, predominantly CBT, for anxiety are more effective when they are delivered by a psychiatrist or clinical psychologist than when delivered by MHNs (Parker et al, 2021). However, to improve access to CBT in Japan, the subsequent FY 2016 revision of medical fees expanded the range of eligible CBT providers to include MHNs.…”
Section: Introductionmentioning
confidence: 99%
“…The most common treatment for anxiety disorders regardless of severity is pharmaceutical management [12]. In addition to being effective, pharmaceutical management also tends to be more accessible than other treatment options [12]. Numerous groups of pharmacological treatments exist for the anxiety disorder.…”
Section: Pharmaceuticals As a Treatment For Anxietymentioning
confidence: 99%
“…Anxiety disorders are common in patients and in the general population [1]. In primary care settings, anxiety disorders are among the most frequent disorders observed [2][3][4], and these disorders are associated with high use of health care services [5]. Sex and age differences in anxiety have been investigated in several studies.…”
Section: Introductionmentioning
confidence: 99%